Evaluation of a student participatory, low-intensity program to improve school wellness environment and students' eating and activity behaviors. Issue 1 (December 2016) - Hoelscher, Deanna; Moag-Stahlberg, Alicia; Ellis, Karen; Vandewater, Elizabeth; Malkani, Raja
Abstract Background Most schools have not fully implemented wellness policies, and those that have rarely incorporate meaningful student participation. The aim of the Fuel Up to Play 60 (FUTP60) program is to help schools implement wellness policies by engaging students in activities to improve access to healthful, good tasting food and drinks, and increase the number and type of opportunities for students to be physically active. The aim of this paper is to present initial student-level results from an implementation of FUTP60 in 72 schools, grades 6–9. Methods The study used a non-controlled pretest/posttest with serial cross-sectional data. School process data and student-level data were collected in fall 2009 (pre-intervention) and spring 2010 (post-intervention). School wellness practices were captured during a baseline needs assessment survey. Validated self-administered questionnaires assessing dietary and physical activity (PA) behaviors were administered to students in grades 6–9 in the 72 pilot schools. Mixed-effects logistic regression controlling for clustering of schools and demographics was used to calculate odds ratios and confidence intervals to evaluate changes pre- and post- intervention. Results All 72 schools implemented FUTP60 during the 2009–2010 school year. Action strategies most frequently chosen by the schools included increasing breakfast participation and new activities before and after school. Positive and significant changes in students' behaviors (n = 32, 482 at pretest and 29, 839 at post-test) were noted for dairy, whole grains, fruit, and vegetable consumption and PA levels pre- and post-intervention (OR 1.05 to 1.27). Students aware of the program at post-test were significantly more likely to report healthier eating and PA behaviors than students unaware of the program (OR 1.1 to 1.34). Conclusions FUTP60 pilot findings indicate that a low intensity program focused on wellness policy implementation is associated with small positive changes in student behaviors, especially when students were aware of the program. Although these initial results are promising, a more rigorous controlled study is warranted as a next step.